Contribution A L’etude De La Biologie Florale De Quelques Rosacees Cultivees De La Region De Constantine (Algerie) - Ahlem, Bousmid; Mouad, Boulacel; Mostef, Benlaribi (European Scientific Journal, ESJ, 2016)
Angiosperms largely dominated the current terrestrial flora, with more than 275,000 species already identified (Meyer et al., 2008). Several major characteristics associated with sexual reproduction distinguish this group of plants, making this the most advanced subphylum Phanerogams(Robert et al., 1998). A quick review of flora reveals the wide variety of shapes and floral structures in different families of angiosperms. This diversity is the basis of the key determination and classification or systematic of flowering plants. Rosaceae that constitute our subject of study have a constant organization and regular flower type 5: 5 sepals, 5 petals, many stamens, one or more carpels. In our work we investigated a few dominant species cultivated in our study area such as: Cydonia oblonga Mill., Eriobotrya japonica Thun., Malus domestica Borkh., Prunus domestica L., Prunus dulcis Mill., Prunus persica L., Pyrus communis L. After collecting flowers and extraction of pollen grains, observations with binocular and light microscope there emerges a diversity materialized ia in: - Flower color; - The presence or absence of fuzz around the reproductive organs that are protected temperatures decreases. This allows for example medlar and almond reproduce during cold periods of the year (December, January, February).